Jane Fonda Redefining Age: A Legacy of Challenging Paradigms - Amiri, Saba (AMERICANA E-journal of American Studies in Hungary, 2024)
This paper aims to capture the legacy of the American actress and activist Jane Fonda from a particular perspective: her attempt to revolutionize the conventional paradigm of aging in her publications Prime Time: Love, Health, Sex, Fitness, Friendship, Spirit: Making the Most of All of Your Life (2011), which lie at the heart of this research. When synthesized, the book offers a paradigm shift in redefining the common narrative of aging, from one dominated by decline – symbolized as the arch – to the metaphorical use of the staircase as a path that celebrates growth.